The Effectiveness of Video “6 Steps Hands Wash” to Improve the Capability Hand Washing for Children with Intellectual Disability - Utami, Annisa Putri; Pujaningsih, Pujaningsih (Department of Special Education, 2021)
This study aims to determine the effectiveness of the